Predators, alternative prey and climate influence annual breeding success of a long‐lived sea duck. (31st January 2013) - Iles, David T.; Rockwell, Robert F.; Matulonis, Paul; Robertson, Gregory J.; Abraham, Kenneth F.; Davies, J. Chris; Koons, David. N.; Smallegange, Isabel
Summary Perturbations to ecosystems have the potential to directly and indirectly affect species interactions, with subsequent impacts on population dynamics and the vital rates that regulate them. The few long‐term studies of common eider breeding ecology indicate that reproductive success is low in most years, interrupted by occasional boom years. However, no study has explicitly examined the drivers of long‐term variation in reproductive success. Here, we use encounter history data collected across 41 years to examine the effects of arctic foxes (a terrestrial nest predator), local abundance and spatial distribution of lesser snow geese (an alternative prey source), and spring climate on common eider nest success. Eider nest success declined over the course of the study, but was also highly variable across years. Our results supported the hypothesis that the long‐term decline in eider nest success was caused by apparent competition with lesser snow geese, mediated by shared predators. This effect persisted even following a large‐scale exodus of nesting geese from the eider colony. Nest success was also lowest in years of low arctic fox index, presumably driven by prey switching in years of low small mammal availability. However, increased snow goose abundance appeared to buffer this effect through prey swamping. The effect of spring climate depended on the stage of the breeding season; cold and wet and warm and dry conditions in early spring were correlated with decreased nest success, whereas warm and wet conditions in late spring increased eider nest success. These results underscore the significance of both trophic interactions and climate in regulating highly variable vital rates, which likely have important consequences for population dynamics and the conservation of long‐lived iteroparous species.